Nivel de educación financiera en estudiantes de la Institución Educativa Primaria N° 60078 Yraida Rojas Regra, Pebas 2021 - Yaicate Yahuarcani, Wiler Rolin (2022)
This research has been carried out in order to describe the level of financial education in primary school students at the public educational institution No. 60078 Yraida Rojas Regra, in the town of Pebas in 2021. The research approach It is quantitative, descriptive, with a transectional, field and univariate design. The population has been made up and the sample with the population and sample considered has been 156 primary school students from the educational institution. The technique was the survey and a questionnaire as a data collection instrument, which was previously validated by experts. The conclusion of the research is that 19.9% of the students participating in the research are located at the low level of financial education; 69.9% at the intermediate level and only 10.3% at the high level, which means that there is much to do regarding promoting knowledge about financial culture in the classrooms of the educational institution.